A red-emissive two-photon fluorescent probe for mitochondrial sodium ions in live tissue - Juvekar, Vinayak; Cho, Myoung Ki; Lee, Hyo Won; Lee, Dong Joon; Kang, Hyuk; Song, Ju Man; Je, Jong Tae; Kim, Hwan Myung (Chemical Communications, 2021)
A cyclocyanine (CC)-based organic small molecule two-photon (TP) fluorescent probe (CCNa1) was developed for mitochondrial sodium ion sensing.CCNa1exhibits a low solvatochromic shift and strong TP fluorescence enhancement at 575 nm upon binding to Na+and is insensitive to other metal ions and to pH.CCNa1demonstrated fast cell loading ability, biocompatibility, and sensitive response to mitochondrial Na+influx in live cells and mouse brain tissue.
Keywords: Cell loading; Fluorescence enhancement; Fluorescent probes; Live tissue; Mouse brain; Organic small molecule; Red emissive; Solvatochromic shifts; Animals; Crown Ethers; Fluorescent Dyes; HeLa Cells; Heterocyclic Compounds, 4 or More Rings; Hippocampus; Humans; Mice; Mitochondria; Photons; Sodium